Performances of Broiler Chickens Fed the Commercial Diets Partially Substituted with Feeds Containing Fermented and Non Fermented Leubim Fish Meal (Canthidermis maculata) - zulfan zulfan; Muhammad Aman Yaman; Allaily Allaily; Enten Juni Marlina (Buletin Peternakan, 2020)
The purpose of present study was to evaluate the performance of broilers fed the commercial diet partially substituted with leubim fish (Canthidermis maculata) waste meal (LFWM) treated by fermentation and without fermentation. As many as 100 broiler chicks, MB 202 strain, unsex, were reared up to 5 weeks in this study. The research was set up into randomized block design (RBD) consisting of 5 treatments and 4 blocks with 5 birds each. Blocks were as replicate based on the body weights of the birds at the beginning of feeding experimental diets. The experimental diets were commercial diets partially replaced with LFWM administered by either fermentation or not with the level of 6 and 12% each, 6.5% and 13% yellow corn, and 0.5% topmix. The data was analyzed using an Analysis of Variance (AOV) and continued by Duncan’s Multiple Range Test (DMRT) only if significant effects were detected among the treatments. The result of recent study indicated that the inclusion of feeds containing LFWM treated by either or not fermented combined with yellow corn and topmix as partially substitution of commercial diets significantly increased (P<0.05) FBW, BWG, feed intake, and protein intake compared to those fed full commercial diet. However, FCR and PER were not significantly affected. DMRT indicated there were no significant diferences in broiler performances fed the feeds containing LFWM treated by fermentation vs without fermentation.